(untitled) (LACCEI, 2024)
In the present investigation, a proposal for the implementation of the maintenance area is developed, since due to the current trend towards the outsourcing of this area by companies in Peru, opportunities for growth have been lost, to strengthen an organizational culture and, above all, all of leaving a base legacy for a future operation that seeks excellence, that is why this implementation aims to reduce operating costs and improve the profitability of the sausage business of the company San Fernando S.A. Through the improvement of the indicators, this research is of the theoretical, applied and causal type while the research method is of the quantitative type.